Development of Interactive Multimedia Based on Android Integrated Problem Based Learning (PBL) to Improve Students’s Mastery of Concepts - Bintarti; Roza Linda; Rasmiwetti (Orbital: Jurnal Pendidikan Kimia, 2024)
The results of the pre-research concept mastery test showed students' low mastery of redox and electrochemical concepts. The aim of this research is to produce an Android-based interactive multimedia product integrated with PBL that is valid, practical and effective in the form of an APK. The research method is Development Research referring to the ADDIE development procedure. The research was conducted in the odd semester of 2022/2023. The research sample are 70 students of class XII MIPA SMA N 10 Pekanbaru.  Data was collected through multiple choice tests, essays, questionnaires. The developed product was validated by 3 material experts, and 3 media experts. The practicality tes was carried out by 4 chemistry teachers, 11 students in the one to one and small group stages. The implementation test was carried out at SMA Negeri 10 Pekanbaru.  The average validation results by material experts were 94.8% with very valid criteria and the average validation results by media experts were 95.8% (very valid). Practicality results for 4 chemistry teachers, it was 91.3 in the very practical category and 88.8% for 11 students in the very practical category. The n-gain test results showed an increase in concept mastery in the experimental class, namely 0.7 in the medium category and the control class with an n gain value of 0.3 (low). Based on the research results, it was concluded that the product that had been developed could increase students' mastery of concepts.